2003
DOI: 10.1053/jhep.2003.50384
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK mediates fibrogenic signal through Smad3 phosphorylation in rat myofibroblasts

Abstract: Mikio Ni~hizawa,~ Hepatic stellate cells (HSCs) spontaneously transdifferentiate into myofibroblast (MFB) -phenotype on plastic dishes. This response recapitulates the features of activation in viva Transforming growth &tor P (TGF-P) plays a prominent role in stimulating liver fibrogenesis by MFBs. In quiescent HSCs, TGF-P signaling involves TGF-P type I receptor (TPRI)-mediated phosphorylation of serine residues within the conserved SSXS motif at the C-terminus of Smad2 and Smad3. The middle linker regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 7 publications
6
128
0
Order By: Relevance
“…[33][34][35][36] Thus, ligands capable of activating MAPKs potentially modulate Smad signaling induced by TGFb. It has recently been demonstrated that p38MAPK activate phosphorylation of Smad3 in the middle linker region, which enhances Smad3/4 complex formation and nuclear translocation, 37 consistent with our finding of diminished Smad3/4 reporter gene activity in the presence of a p38MAPK inhibitor. Such phosphorylation by MAPKs in the Smad3 linker region is reportedly required for the full activation of Smad signaling.…”
Section: Tgfb Signal Transductionsupporting
confidence: 93%
“…[33][34][35][36] Thus, ligands capable of activating MAPKs potentially modulate Smad signaling induced by TGFb. It has recently been demonstrated that p38MAPK activate phosphorylation of Smad3 in the middle linker region, which enhances Smad3/4 complex formation and nuclear translocation, 37 consistent with our finding of diminished Smad3/4 reporter gene activity in the presence of a p38MAPK inhibitor. Such phosphorylation by MAPKs in the Smad3 linker region is reportedly required for the full activation of Smad signaling.…”
Section: Tgfb Signal Transductionsupporting
confidence: 93%
“…It has been shown that p38 MAPK was activated by TGF-β1 in hepatic stellate cells, and p38 MAPK phosphorylated Smad3 and promoted the nuclear translocation of Smad3/Smad4 [Furukawa et al, 2003]. In addition, inhibition of p38 MAPK by SB203580 and SB 202190 decreased α-SMA expression in pancreatic stellate cells [Masamune et al, 2003].…”
Section: Nicotine Inhibited Tgf-β1-induced P38 Mapk Activitymentioning
confidence: 99%
“…10,11 Although several studies of EMT have suggested that the process involves Smad-independent pathways, 12 recent studies using Smad3 knockout mice have indicated that signaling through the Smad3-dependent pathway is required for injury-dependent multistage transition of an epithelial cell to a mesenchymal phenotype. 13 We therefore have focused on Smad3 signaling, 14,15 and have recently reported different roles of Smad3 phosphoisoform-mediated signaling in epithelial cells and mesenchymal cells. 16,17 Thus, TGF-␤ activates not only TGF-␤ type I receptor (T␤RI) but also c-Jun N-terminal kinase (JNK), converting Smad3 into two distinctive phosphoisoforms: C-terminally phosphorylated Smad3 (pSmad3C) and linker-phosphorylated Smad3 (pSmad3L).…”
mentioning
confidence: 99%